Encyclopedia of nanoscience and nanotechnology - Nalwa, Hari Singh, 1954-; Smalley, Richard E. (Stevenson Ranch, Calif. : American Scientific Publishers, 2004)
Vol. 1. A-Ch -- v. 2. Cl-E -- v. 3. El-H -- v. 4. Hy-M -- v. 5. Mag-Mu -- v. 6. Nano A-M -- v. 7. Nano Me-T -- v. 8. Ne-P -- v. 9. Po-S -- v. 10. So-Z. Index